Integrating Earth–life systems: a geogenomic approach. (April 2022) - Dolby, Greer A.; Bennett, Scott E.K.; Dorsey, Rebecca J.; Stokes, Maya F.; Riddle, Brett R.; Lira-Noriega, Andrés; Munguia-Vega, Adrian; Wilder, Benjamin T.
Abstract : For centuries, scientists have recognized and worked to understand how Earth's mutable landscape and climate shape the distribution and evolution of species. Here, we describe the emerging field of geogenomics, which uses the reciprocal and deep integration of geologic, climatic, and population genomic data to define and test cause–effect relationships between Earth and life at intermediate spatial and temporal scales (i.e., the mesoscale). Technological advances now power the detailed reconstruction of landscape and evolutionary histories, but transdisciplinary collaborations and new quantitative tools are needed to better integrate Earth–life data. Geogenomics can help build a more unified theory and characterize the boundary conditions under which geologic and climatic processes generate new biodiversity, how species' responses differ, and why. Highlights: Considering Earth's complex and co-occurring geologic and climatic processes is important for understanding species evolution. Use of genome-scale sequence data helps identify which geologic and climatic forces shaped adaptation and divergence of populations and sister species. The emerging field of geogenomics emphasizes independent, testing of non-mutually exclusive hypotheses using deep, reciprocal integration of Earth and evolutionary sciences. Geogenomics offers a new framework for understanding the boundary conditions under which geologic and climatic processes shape the evolution of species. A geogenomics approach can reveal the biological traits that make species more or less responsive to landscape and climate change.